Engineering 2D Materials: A Viable Pathway for Improved Electrochemical Energy Storage. Issue 45 (22nd October 2020) - Lin, Liangxu; Chen, Jun; Liu, Dezheng; Li, Xifei; Wallace, Gordon G.; Zhang, Shaowei
Abstract: Electrochemical energy storage (EES) plays a critical role in tackling climate change and the energy crisis, unfortunately it faces several challenges. Unlike conventional electrode materials which are gradually approaching their capacity limit, the emerging atomically thin 2D materials can potentially open up various new possibilities for design and fabrication of novel EES devices. The studies in this area to date have laid the groundwork in understanding fundamental physics and chemistry of 2D materials, enabling a toolbox of engineering strategies to be used to improve the EES performance. This report reviews recent progress in engineering 2D materials for EES applications. Both theoretical and experimental investigations in this area are summarized, and pathways toward improved EES performance and their novel applications are highlighted based on appropriate integration of promising strategies such as the surface activation, chemical doping, phase engineering, and hybrid structures. Abstract : Building on fundamental understandings of the electrochemical energy storage process and the particular surface physics and chemistry of various 2D materials, the key engineering strategies for the improvement of energy storage performance are critically reviewed, providing clear and straightforward pathways toward improved energy storage devices relying upon these 2D materials.